NON-LIGATION OF INDIRECT HERNIAL SAC IN CHILDREN - Ali, Kishwar; Kamran, Haider; Khattak, Irfan Ud-Din; Latif, Humera (Journal of Ayub Medical College Abbottabad, 2015)
Background: It is still a matter of debate whether to ligate the indirect hernial sac during herniotomy or leave it open. We designed this study to find out the complications associated with leaving the sac open. Methods: This observational study was carried out at Surgical Unit C, Ayub Medical College, Abbottabad from January 2007 to December 2012. The hernial sacs of some children, aged 5 months to 12 years, undergoing herniotomies were left open, and these children were closely followed for development of complications especially early recurrence, due to this non-ligation of hernial sac. Results: A total of 23 male children who underwent herniotomies for indirect inguinal hernia and undescended testes were included in the study. No early or late hernia recurrence was observed in these children although minor complications like wound infection and seroma were noted in 2 children. Conclusion: Excision of the hernia sac and leaving the stump open is safe and effective with no early recurrence. Keywords: Non ligation, Hernial sac, Herniotomy